2016
DOI: 10.1016/j.bpobgyn.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine bleeding

Abstract: Abnormal uterine bleeding (AUB) is a common and debilitating condition with high direct and indirect costs. AUB frequently co-exists with fibroids, but the relationship between the two remains incompletely understood and in many women the identification of fibroids may be incidental to a menstrual bleeding complaint. A structured approach for establishing the cause using the Fédération International de Gynécologie et d'Obstétrique (FIGO) PALM-COEIN (Polyp, Adenomyosis, Leiomyoma, Malignancy (and hyperplasia), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 41 publications
5
134
1
11
Order By: Relevance
“…12 In the present study,10.4% of cases of AUB was caused by polyps. Similarly, study done by Doraiswamy et al also showed that polyps accounted for 11.2% cases of AUB.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…12 In the present study,10.4% of cases of AUB was caused by polyps. Similarly, study done by Doraiswamy et al also showed that polyps accounted for 11.2% cases of AUB.…”
Section: Discussionsupporting
confidence: 47%
“…Intrauterine contraceptive device (IUD) may cause low grade endometritis and also cause unbalanced ratios of prostaglandins and thromboxanes which may contribute to AUB. 12 Iatrogenic causes contributed to 11.6% of cases of AUB. The category not yet classified is reserved for entities like chronic endometritis, myometrial hypertrophy which contributed to 1.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leiomyoma is the most common benign smooth muscle tumor of the female genital tract. 1,2 It is composed of smooth muscle cells and varying amount of fibrous connective tissue, common in the reproductive age group. 3 Unopposed estrogenic stimulation causes secondary changes in leiomyomas along with associated endometrial proliferation or hyperplasia.…”
Section: Introductionmentioning
confidence: 99%